1999
DOI: 10.1002/(sici)1097-4644(19990401)73:1<106::aid-jcb12>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

1?,25-Dihydroxy-3-Epi-vitamin D3, a natural metabolite of 1?,25-dihydroxyvitamin D3, is a potent suppressor of parathyroid hormone secretion

Abstract: 1Alpha,25(OH)2D3 is an important negative regulator of parathyroid hormone (PTH) gene transcription. In parathyroid cells, as in other target tissues, 1alpha,25(OH)2D3 is degraded by side chain oxidation by the inducible 24-hydroxylase. We have previously shown that one metabolite of this pathway, 1alpha,23(S),25-(OH)3-24-oxo-D3, potently suppresses PTH synthesis and secretion in cultured bovine parathyroid cells (bPTC). Further examination of the metabolites of 1alpha,25(OH)2D3 in bPTC has revealed another co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
53
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(56 citation statements)
references
References 24 publications
(30 reference statements)
3
53
0
Order By: Relevance
“…These findings imply that C-3 epimerization pathway is cell-selective and contributes to the metabolism of vitamin D in concert with the C-23/C-24 hydroxylation pathways. It is interesting to note that 3-epi-1␣,25(OH) 2 D 3 was almost equipotent to 1␣,25(OH) 2 D 3 in suppressing parathyroid hormone secretion in bovine parathyroid cells (36) and in inhibiting keratinocyte proliferation (24,37), and more potent than 1␣,25(OH) 2 D 3 in inducing HL-60 cell apoptosis (38). In addition, a high metabolic stability of 3-epi-1␣,25(OH) 2 D 3 in target cells has been proposed by Reddy et al (30).…”
Section: Discussionmentioning
confidence: 99%
“…These findings imply that C-3 epimerization pathway is cell-selective and contributes to the metabolism of vitamin D in concert with the C-23/C-24 hydroxylation pathways. It is interesting to note that 3-epi-1␣,25(OH) 2 D 3 was almost equipotent to 1␣,25(OH) 2 D 3 in suppressing parathyroid hormone secretion in bovine parathyroid cells (36) and in inhibiting keratinocyte proliferation (24,37), and more potent than 1␣,25(OH) 2 D 3 in inducing HL-60 cell apoptosis (38). In addition, a high metabolic stability of 3-epi-1␣,25(OH) 2 D 3 in target cells has been proposed by Reddy et al (30).…”
Section: Discussionmentioning
confidence: 99%
“…Parathyroid glands are reported to contain VDR (Naveh-Many et al, 1990;Brown et al, 1992bBrown et al, , 1995Demay et al, 1992;Hellman et al, 1999), and therefore the observed distribution of radioactivity may reflect binding of [1␤-3 H]F 6 -1␣,25(OH) 2 VD 3 and [1␤-3 H]1␣,25(OH) 2 VD 3 . Brown et al (1992aBrown et al ( , 1999 earlier reported that in parathyroid cells, as in other target tissues, 1␣,25(OH) 2 VD 3 was degraded by side chain oxidation, suggesting that the inducible 24-hydroxylase is responsible. Recently, reverse-transcription polymerase chain reaction and immunohistochemical analyses showed expression of 1␣-hydroxylase in both normal and pathological parathyroid tissue, and the findings imply that in addition to feedback control by circulating 1␣,25(OH) 2 VD 3 levels, parathyroid cells may also be influenced by local 1␣-hydroxylase activity with possible growthregulatory effects (Segersten et al, 2002).…”
Section: Parathyroidmentioning
confidence: 97%
“…The metabolism of C-3 epimers has not been fully understood. Reddy et al (32) reported that 3-epi-1␣,25(OH) 2 D 3 was metabolized to three polar metabolites, 3-epi-1␣,24,25 (OH) It was reported that 3-epi-1␣,25(OH) 2 D 3 suppresses parathyroid hormone secretion in cultured bovine parathyroid cells (12) and induces surfactant phospholipid synthesis in pulmonary alveolar type II cells (34) irrespective of its low binding affinity to VDR. High metabolic stability of 3-epi-1␣,25(OH) 2 D 3 has been proposed as a possible explanation for the parathyroid hormone-suppressing and surfactant phospholipid-inducing effects of 3-epi-1␣,25(OH) 2 D 3 in vitro.…”
Section: Metabolism Of 25(oh)d 3 In Umr 106mentioning
confidence: 99%
“…1␣,25(OH) 2 D 3 has potent anti-proliferative and cell differentiation-inducing activities in addition to its role in calcium homeostasis. After the expression of various biological activities, 1␣,25(OH) 2 D 3 is further metabolized through the C-24 (3-6)/C-23 (7-10) oxidation pathways and the C-3 epimerization pathway (11)(12)(13)(14). The C-24 oxidation pathway, initiated by C-24 hydroxylation, leads to the conversion of 1␣,25(OH) 2 D 3 into a side chain cleavage product, calcitroic acid (4,5).…”
mentioning
confidence: 99%
See 1 more Smart Citation